Uso de Estrategias Metodológicas en la planificación curricular de 10 docentes del área de Educación Física en la Básica Superior para favorecer el aprendizaje en la modalidad virtual en la ciudad de Riobamba durante el periodo Julio – Octubre 2021. - Castro Morales, Francis Anahí (2022)
After a year of confinement due to the global pandemic, all the Schools were forced to had classes in virtual mode. Hence all the areas of education had to use different methodological strategies. This study focuses specifically on the Physical Education Teachers who teach the content with the Higher Basic (8th, 9th, 10th). With the application of “Priorized Curriculum for the Emergency” proposed by the Ministry of Education, there were many changes, one of the most important was the way to plan. This research aims to analyze the methodological strategies that Physical Education Teachers used for virtual modality and to determine which micro curricular planning they carried out. The implementation of this project is descriptive bibliographic; using the deductive method to reach the different conclusion raised in the specific objectives of the research. Within the Physical Education Teachers population, 10 of the them were chosen by the other high schools to be part of this research. So, the instrument that were used were an observation sheet and a question questionnaire for the interview. Therefore, the study showed that the most teachers in the area of Physical Education used the different planning of the micro-planning for the virtual modality.